Montaje de una red de Hostales en el Departamento de Boyacá (2013)
The project consists of the assembly of a lodging network composed of 10 hostels, located in the Department of Boyacá, Colombia. A business opportunity has been identified in the tourism sector in this Department due to its great potential, as it has a great cultural, artisanal and architectural history, as well as having in its territory natural parks, lagoons, reservoirs, rivers and numerous natural waterfalls. The growth of tourism in Colombia in recent years generates different needs to be addressed; specifically in Boyacá there is no organized chain of hostels where the user can register and sharpen to access different benefits, so generating a lodging option in different places within the Department becomes a requirement to help meet the objectives of the country in relation to tourism. The main feature of this type of hosting is the low cost that the user must pay per night, obtaining a high quality service. Hostel is understood as the definition presented by the Icontec Colombian Sectorial Technical Standard NTSH 006: "A hostel is an establishment in which the hosting service is provided preferably in semi-private or common rooms, as well as its bathrooms, and which may also have, of a common room adequately equipped for guests to prepare their own food, without prejudice to provide other complementary services. "